Aging Prisoners' Views on Healthcare Services in Swiss Prisons. (March 2019) - Galli, Serena; Bretschneider, Wiebke; Elger, Bernice Simone; Handtke, Violet; Shaw, David
Objective: Due to the higher morbidity prevalent in the increasing older population, prisons are facing new challenges on a structural, ethical, and financial level. This study's goal was to explore older prisoners' views and experiences regarding the quality of medical services.Method: In this qualitative study, 35 semi-structured interviews were conducted with older inmates aged 50 years and above in 12 different prisons in the German-speaking (23 interviews) and the French-speaking parts (12 interviews) of Switzerland.Results: The majority of older prisoners in this sample expressed concerns about quality of treatment throughout incarceration. Topics addressed reached from quality of the entrance to routine examinations, quality of the treatment received, and delays in care and services provided.Conclusion: This study's findings suggest that healthcare in prison is often perceived as insufficient and inadequate by older inmates.